1991
DOI: 10.1113/jphysiol.1991.sp018561
|View full text |Cite
|
Sign up to set email alerts
|

Role of peptidoleukotrienes in capsaicin‐sensitive sensory fibre‐mediated responses in guinea‐pig airways.

Abstract: SUMMARY1. The right bronchus with the right vagus nerve remaining intact was isolated from the guinea-pig. Stimulating the end of the right vagus nerve distal to the bronchus resulted in a biphasic contractile response with a rapid first phase and a second phase which persisted after the cessation of stimulation. The first phase was selectively sensitive to atropine, while the second phase was non-cholinergic, but abolished by pre-treatment with the sensory C fibre toxin, capsaicin. This biphasic contraction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 27 publications
1
23
1
1
Order By: Relevance
“…While this approach has the advantage noted above, it does remove the Cfiber from extraneuronal influences that are ordinarily present within the intact airway. It is well established that various compounds can "sensitize" or inhibit C-fiber activation by other stimulants (21)(22)(23)(24). It is possible that the absence of such a m 30-50 -e compounds which might be present within intact airways altered the responses we observed in cultured DRG cells.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…While this approach has the advantage noted above, it does remove the Cfiber from extraneuronal influences that are ordinarily present within the intact airway. It is well established that various compounds can "sensitize" or inhibit C-fiber activation by other stimulants (21)(22)(23)(24). It is possible that the absence of such a m 30-50 -e compounds which might be present within intact airways altered the responses we observed in cultured DRG cells.…”
Section: Discussioncontrasting
confidence: 38%
“…Perhaps mechanical coupling, rather than direct neuronal activation, explains how some or all of the mediators studied led to tachykinin release. Other studies have also concluded that administration of various inflammatory mediators (21)(22)(23)(24)(25)(26)(27) or even hypertonic saline (28) stimulate C-fibers to release tachykinins in the airways. Yet because airways contain many cell types capable of releasing their own compounds which might directly stimulate sensory g; 600-Q 400-L.. C-fibers, and because of the potential for mechanical coupling noted above, it is difficult to be sure whether or not the effect of a putative C-fiber stimulant is actually a direct one.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is evidence for a tonic cysLT 1 receptor mediated regulation of airways in guinea pigs [58,59]. In both species, this basal tone mediated by autacoids appears to be manifest both in vivo and in vitro [58,[60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the histamine H 1 receptor-selective antagonist pyrilamine could prevent and reverse the antigen-induced potentiation. Other mast cell mediators such as the cysteinyl leukotrienes (Cys -LTs) may also contribute to allergen-induced potentiation of tachykinergic nerve-mediated responses in the airways via the activation of Cys-LT 1 receptors on afferent nerve endings (70,75,76).…”
Section: Enhanced Release Of Tachykininsmentioning
confidence: 99%